Current treatment of acute perforated diverticulitis: the role of damage control surgery - Zizzo M; Manenti A; Ugoletti L (Dove Medical Press, 2018)
Maurizio Zizzo,1,2 Antonio Manenti,3 Lara Ugoletti,11Department of Oncology and Advanced Technologies, Surgical Oncology Unit, AUSL-IRCCS of Reggio Emilia - Arcispedale Santa Maria Nuova, Reggio Emilia, Italy; 2Clinical and Experimental Medicine PhD Program, University of Modena and Reggio Emilia, Modena, Italy; 3Department of General Surgery, Azienda Ospedaliero-Universitaria - Policlinico, Modena, ItalyWe were struck by Ceresoli et al’s1 article published in Journal of Inflammation Research in May 2018. The aim of the review was to investigate the role of inflammation in diverticular disease and in mild and complicated acute diverticulitis with particular attention to the current research and treatment perspectives.1 Based on the solid collaboration of the authors with the World Society of Emergency Surgery (WSES), a worldwide reference in the management of emergency surgical diseases, our attention was focused on the Damage Control Surgery (DCS) paragraph.View the original paper by Ceresoli and colleagues.